Penyuluhan Kesehatan Gigi dan Mulut Bagi Siswa di Kecamatan Sembalun, Lombok Timur, Nusa Tenggara Barat - Yuditha, Solva; Kusparmanto, Lukas; Dewi, Komang Krisna (Universitas Prof. Dr. Moestopo (Beragama), 2022)
Dental and oral health is an important indicator to determine overall body health. Dental and oral health can affect the health of a person's body so efforts are needed to maintain good dental and oral health. This problem will result in the metabolic activity of bacteria and plaque which causes tooth decay, in the long term it will cause tooth loss and will eventually cause masticatory function disorders. Dental Alumni Association, Faculty of Dentistry, University of Prof. Dr. Moestopo (Beragama) Jakarta has the idea to carry out social service activities with the aim of participating in the success of government programs, especially the Ministry of Health to create caries free Indonesian society at the age of 12 which is targeted for 2030. Social service activities are carried out at SDN 1 and SMPN 1 Sembalun, East Lombok, West Nusa Tenggara with a target of 200 elementary school students and 207 junior high school students. The implementation method used is in the form of dental and oral health counseling, distribution of toothbrushes and toothpaste as well as joint tooth brushing activities in an effort to prevent dental caries by brushing the teeth properly.